Light pollution : consequences and sustainable lighting design - Insulander, Anna Maria (SLU/Dept. of Urban and Rural Development, 2012)
Light has always fascinated humans but ever since the invention of the first light bulb, the use of artificial lighting has accelerated dramatically. Darkness has never been as rare as today and the overuse of lighting has created a new phenomenon called light pollution. Most living beings are biologically dependent on the recurrent twenty-four-hour rhythm of light and darkness, called the circadian cycle. Human beings are evolutionary developed after this circadian rhythm and the effects of constant artificial light is yet unknown. Scientists fear the consequences of constant lighting and what it means physically, mentally and philosophically for the human species. New science show that the absent of darkness not only affect the sleep but might also lead to an increased risk of diabetes and cancer. Even animals and plants are controlled by the circadian cycle. Light pollution has therefore a great influence on nocturnal animals. The loss of darkness has influences on fundamental biological systems that scientists do not know the consequences of. Light pollution is therefore a crucial aspect for landscape architects to consider while designing with lighting. The purpose of my bachelor essay is to map out the negative consequences of light pollution. I chose to perform the research by literature studies but also through conversations with skilled people working with light. The results of the literature study showed sincerely negative effects of light pollution on wildlife and humans. The conversations with light designers and landscape architects gave though another point of view on light pollution. The results of the conversations also gave some easy aspects to be considered to reduce light pollution while designing with lighting. My essay finally discusses light pollution as a global potential threat that has to be considered while designing on the smaller scale.